Creating the intellectual : Chinese communism and the rise of a classification - U, Eddy (University of California Press, 2019)
"Creating the Intellectual redefines how we understand relations between intellectuals and the Chinese socialist revolution of the last century. Under the Chinese Communist Party, "the intellectual" was first and foremost a widening classification of individuals based on Marxist thought. The party turned revolutionaries and otherwise ordinary people into subjects identified as usable but untrustworthy intellectuals. The appearance of such subjects profoundly affected patterns of domination, interaction, and rupture within the revolutionary enterprise. Drawing on a wide range of data, Eddy U takes the reader on a journey that examines political discourses, revolutionary strategies, rural activities, urban registrations, workplace arrangements, organized protests, and theater productions. He lays out in colorful detail the formation of new identities in Chinese society and new forms of organization and association. The outcome is a compelling picture of the mutual constitution of the intellectual and the Chinese socialist revolution, the legacy of which still affects ways of seeing, thinking, acting, and feeling in what is now a globalized China"--Provided by publisher.